Management of Giant Calcified Thoracic Disks and Description of the Trench Vertebrectomy Technique. (September 2016) - Al-Mahfoudh, Rafid; Mitchell, Paul S.; Wilby, Martin; Crooks, Daniel; Barrett, Chris; Pillay, Robin; Pigott, Tim
Study Design: Case series and review of the literature. Objective: To review the management of giant calcified disks in our large cohort and compare with the existing literature. We discuss our surgical technique. Methods: Twenty-nine cases of herniated thoracic disk between 2000 and 2013 were reviewed. Eighteen patients were identified as having giant calcified thoracic disks, defined as diffusely calcified disks occupying at least 40% of the spinal canal. Demographic data was collected in addition to presentation, imaging findings, operative details, and outcomes using the modified Japanese Orthopaedic Association (mJOA) scale. Results: Giant calcified thoracic disks (GCTDs) are unique clinical entities that require special neurosurgical consideration owing to significant (≥40%) involvement of the spinal canal and compression of the spinal cord, often leading to myelopathy. The median age at diagnosis was 51.2 years (range 37 to 70) with the mean duration of presenting symptoms being 9.9 months (range 2 weeks to 3 years). Seventeen (94.4%) patients presented with at least one sign of myelopathy (hyperreflexia, hypertonia, bladder or bowel dysfunction) with the remaining 1 (5.6%) patient presenting with symptoms in keeping with radiculopathy. Thoracotomy was performed on 17 (94.4%) patients, and 1 (5.6%) patient had a costotransverse approach. Mean follow-up was 19.8 months (range 7 months to 2 years). mJOA score improved in 15 (83.3%) patients. mJOA scores in the other patients remained stable. Conclusions: GCTDs are difficult neurosurgical challenges owing to their size, degree of spinal cord compression, and consistency. We recommend a trench vertebrectomy via a thoracotomy in their surgical management. This procedure safely allows the identification of normal dura on either side of the compressed segment prior to performing a diskectomy. Excellent fusion rates were achieved with insertion of rib head autograft in the trench.